Inventory of the adult student 25 years of age and older at the University of Wisconsin - La Crosse - Schroeder, Signe (My University, 1974)
The purpose of this paper was to inventory the demographic data of students 25 years of age and older enrolled at the University of Wisconsin-La Crosse for the second semester 1973-74, and to seek information from these students regarding their reasons for seeking higher education, what services they had occasion to use, how satisfied they were with their experiences at the University and what their overall evaluation of their experience was. A 10 percent random sample of undergraduate students 25 years of age and older and a 10 percent random sample of graduate students 25 years of age and older were used in this study. A total of 119 students were sent identical questionnaires of which 58 (49 percent) were returned. Of the 10 percent random sampling returning the questionnaires, 27 (36 percent) were undergraduates and 31 (68 percent) were graduate students. Fifty-five percent were female and 68 percent were married. The largest age group represented ranged from 25 to 35 years (58. 6 percent). The largest group of students (31 percent) were graduates working in special categories. The next largest group were undergraduates (24 percent) working toward a degree. The credit load was evenly divided among students ? one-third were taking 1 to3 credits, one-third were taking 3 to 12 credits, and another third were taking 12 credits and more. Answers were charted as to why students 25 years and older were seeking further education, what services they had had occasion to use, how satisfied they were with various facets of their University experience, and their overall evaluation. Each question was discussed with regard to age, sex, and University status.
Keywords: Non-traditional college students -- Wisconsin -- La Crosse; University of Wisconsin--La Crosse -- Students